Theology and Culture : A Guide to the Discussion - Long, D. Stephen (Eugene. : : Cascade Books, 2008)
"Published by arrangement with Cascade Books..." Includes questions for reflection after each chapter. Includes bibliographical references (p. 113-114)
Theology and culture: the promises and perils -- What is culture? -- Confusing nature and culture -- Language -- Diverse uses of "culture" -- Culture and God -- Theologians and culture I: the work of Ernst Troeltsch -- Theologians and culture II: H. Richard Niebuhr's typology -- Theologians and culture III: Paul Tillich's Protestant principle -- Theology, modernity, and postmodernity -- Contemporary theology I: post-liberal, analytical, post-modern feminist -- Contemporary theology II: radical orthodoxy, Communio Catholicism, Anabaptist witness
Keywords: Christianity and culture; Christianity and culture -- History -- 20th century